A 30-Year Prospective Follow-Up Study Reveals Risk Factors for Early Death in Cartilage-Hair Hypoplasia - Vakkilainen, Svetlana; Taskinen, Mervi; Klemetti, Paula; Pukkala, Eero; Mäkitie, Outi (Frontiers in Immunology, 2019)
Cartilage-hair hypoplasia (CHH) is a skeletal dysplasia with combined immunodeficiency, variable clinical course and increased risk of malignancy. Management of CHH is complicated by a paucity of long-term follow-up data, as well as knowledge on prognostic factors. We assessed clinical course and risk factors for mortality in a prospective cohort study of 80 patients with CHH recruited in 1985-1991 and followed up until 2016. For all patients we collected additional health information from health records and from the national Medical Databases and Cause-of-death Registry. The primary outcome was immunodeficiency-related death, including death from infections, lung disease and malignancy. Standardized mortality ratios (SMRs) were calculated using national mortality rates as reference. Half of the patients (57%, n=46) manifested no symptoms of immunodeficiency during follow-up while 19% (n=15) and 24% (n=19) demonstrated symptoms of humoral or combined immunodeficiency, including six cases of adult-onset immunodeficiency. In a significant proportion of patients (17/79, 22%), clinical features of immunodeficiency progressed over time. Of the 15 patients with non-skin cancer, eight had no preceding clinical symptoms of immunodeficiency. Altogether 20 patients had deceased (SMR=7.0, 95%CI=4.3-11); most commonly from malignancy (n=7, SMR=10, 95%CI=4.1-21) and lung disease (n=4, SMR=46, 95%CI=9.5-130). Mortality associated with birth length below -4 standard deviation (compared to normal, SMR/SMR ratio=5.4, 95%CI=1.5-20), symptoms of combined immunodeficiency (compared to asymptomatic, SMR/SMR ratio=3.9, 95%CI=1.3-11), Hirschsprung disease (odds ratio (OR) 7.2, 95%CI=1.04-55), pneumonia in the first year of life or recurrently in adulthood (OR=7.6/19, 95%CI=1.3-43/2.6-140) and autoimmunity in adulthood (OR=39, 95%CI=3.5-430). In conclusion, patients with CHH may develop adult-onset immunodeficiency or malignancy without preceding clinical symptoms of immune defect, warranting careful follow-up. Variable disease course and risk factors for mortality should be acknowledged.